Customer-Based Brand Equity for Tourist Destinations: A Comparison of Equities of Puerto Rico and the US Virgin Islands - Marta Almeyda (Journal of Spatial and Organizational Dynamics, 2020)
Historically, the Caribbean tourism destinations have competed based on their largely undifferentiated marketing mix. More recent evidence from the Caribbean tourism promotional practice, however, indicates the realization in the practitioner community that developing a distinct brand equity is critical for success. This paper aims to identify and measure elements of brand equity for Puerto Rico and the US Virgin Islands, compare the brand equity of the two destinations, and provide branding recommendations. In this study, these destinations were subjected to a customer-based brand equity for tourism destinations (CBBETD) model comprising the five dimensions of brand equity – i.e., social image, price/value, trustworthiness, identification/attachment, and brand performance. The CBBETD scores were then compared in order to understand better the differences in brand equity between these two similarly placed US territories in the Caribbean.